Home Computers and Child Outcomes: Short-Term Impacts from a Randomized Experiment in Peru - Diether Beuermann; Julian Cristia; Yyannu Cruz-Aguayo; Santiago Cueto; Ofer Malamud (Inter-American Development Bank (IDB), 2012)
This paper presents results from a randomized control trial in which approximately 1,000 OLPC XO laptops were provided for home use to children attending primary schools in Lima, Peru. The intervention increased access and use of home computers, with some substitution away from computer use outside the home. Beneficiaries were more likely to complete domestic chores but less likely to read books. Treatment children scored almost one standard deviation higher in a test of XO proficiency, though there were no effects on objective and self-reported skills for using a Windows-based PC and Internet. There were positive impacts on the Raven's Progressive Matrices test among children who did not have a home computer before the intervention, but no significant effects for the sample as a whole. Finally, there was little evidence for spillovers within schools, although close friends and classmates of laptop recipients did exhibit higher proficiency with the XO computer.
Keywords: C93; I21; I28; 330